Clinical course of primary HIV infection: consequences for subsequent course of infection. Issue 6692 (15th July 1989) - Pedersen, C.; Lindhardt, B. O.; Jensen, B. L.; Lauritzen, E.; Gerstoft, J.; Dickmeiss, E.; Gaub, J.; Scheibel, E.; Karlsmark, T.
Abstract : OBJECTIVE--To investigate the impact of the clinical course of the primary HIV infection on the subsequent course of the infection. DESIGN--Prospective documenting of seroconversion, follow up at six month intervals, and analysis of disease progression by life tables. PATIENTS--86 Men in whom seroconversion occurred within 12 months. PRIMARY OUTCOME MEASURE--Progression of HIV infection, defined as CD4 lymphocyte count less than 0.5 X 10(9)/l, recurrence of HIV antigenaemia, or progression to Centers for Disease Control group IV. MAIN RESULTS--Median follow up was 670 (range 45-1506) days. An acute illness like glandular fever occurred in 46 (53%) subjects. Three year progression rates to Centers for Disease Control group IV was 78% at three years for those who had longlasting illnesses (duration greater than or equal to 14 days) during seroconversion as compared with 10% for those who were free of symptoms or had mild illness. All six patients who developed AIDS had had longlasting primary illnesses. Three year progression rates to a CD4 lymphocyte count less than 0.5 X 10(9)/l and to recurrence of HIV antigenaemia were significantly higher for those who had longlasting primary illnesses than those who had no symptoms or mild illness (75% v 42% and 55% v 14%, respectively). CONCLUSION--The course of primary infection may determine the subsequent course of the infection.